Strengthening Food Systems Resilience and Agricultural Trade in Southern Africa - Bulwani, Gideon; Magagula, Futhi; Mwale, Simon (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate change and its impact on agricultural production and productivity is a major factor of concern in the agricultural sector. Many indicators point to the significant depressing role that climate change has on the agricultural sector, spanning from production to marketing of the primary and secondary products. Women and youth comprise most of the rural population in the Southern African Development Community (SADC) region and likely to be more affected by the impacts of climate change in the agricultural sector. Therefore, any interventions must ensure deliberate efforts to empower these stakeholders to ensure their equitable participation and benefit from development interventions. Recent discourse on sustainable food systems heightened discussions on alternative productions systems. Some international development agencies such as Food and Agriculture Organization (FAO) highlighted the possible role for agroecology to contribute towards achieving the Sustainable Development Goals (SDGs) because it addresses climate change adaptation and mitigation simultaneously. Despite increasing interest by development partners and other stakeholders on agroecology, there has been limited dialogue on this subject at SADC region level. The Centre for Coordination of Agriculture Research and Development for Southern Africa (CCARDESA) is taking steps to raise the capacity of the region to adapt to climate change and improve resilience of the food systems of the region. This effort is being pursued through various programs, including the Comprehensive Africa Agriculture Development Programme (CAADP) ex-Pillar IV (CAADP-XP4) program, the Global Climate Change Alliance Plus (GCCA+) project and the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project. Therefore, CCARDESA convened a regional workshop to consult the region and give an opportunity to stakeholders to provide input to the work of CCARDESA relating to cross border trade, agroecology, and climate smart agriculture as well as the involvement of the private sector in promoting Climate Smart Agriculture (CSA). The meeting was also used to distil CSA issues for the forthcoming Conference of Parties (COP) 27.